Early postnatal testosterone predicts sex-related differences in early expressive vocabulary. (June 2016) - Kung, Karson T.F.; Browne, Wendy V.; Constantinescu, Mihaela; Noorderhaven, Rebecca M.; Hines, Melissa
Highlights: There was a sex difference in salivary testosterone in infants aged 1–3 months. Testosterone in infancy predicted vocabulary in boys and in girls in toddlerhood. The sex difference in vocabulary was mediated by testosterone in infancy. Testosterone in infancy may contribute to early language development. Abstract: During the first few years of life, girls typically have a larger expressive vocabulary than boys. This sex difference is important since a small vocabulary may predict subsequent language difficulties, which are more prevalent in boys than girls. The masculinizing effects of early androgen exposure on neurobehavioral development are well-documented in nonhuman mammals. The present study conducted the first test of whether early postnatal testosterone concentrations influence sex differences in expressive vocabulary in toddlers. It was found that testosterone measured in saliva samples collected at 1–3 months of age, i.e., during the period called mini-puberty, negatively predicted parent-report expressive vocabulary size at 18–30 months of age in boys and in girls. Testosterone concentrations during mini-puberty also accounted for additional variance in expressive vocabulary after other predictors such as sex, child's age at vocabulary assessment, and paternal education, were taken into account. Furthermore, testosterone concentrations during mini-puberty mediated the sex difference in expressive vocabulary. These results suggest that testosterone during the early postnatal period contributes to early language development and neurobehavioral sexual differentiation in humans.